Efficacy of retinol palmitate eye drops for dry eye in rabbits with lacrimal gland resection - Odaka A (Dove Medical Press, 2012)
Akito Odaka,1 Hiroshi Toshida,2 Toshihiko Ohta,2 Nobuhito Tabuchi,3,4 Daisuke Koike,4 Chikako Suto,3 Akira Murakami31Human and Environmental Safety Evaluation Center, Lion Corporation, Kanagawa, Japan; 2Department of Ophthalmology, Juntendo University Shizuoka Hospital, Shizuoka, Japan; 3Department of Ophthalmology, Juntendo University School of Medicine, Tokyo, Japan; 4Pharmaceutical Research Laboratories No 1, Research and Development Headquarters, Lion Corporation, Kanagawa, JapanPurpose: We examined the efficacy of retinol palmitate (VApal) for dry eyes using dry eye model rabbits whose lacrimal glands were resected.Materials and methods: After alkaline injury on keratoconjunctival epithelium, VApal eye drops were administered 6 times a day for 7 days. The efficacy of VApal was also compared with that of 0.1% hyaluronic acid eye drops.Results: The fluorescein staining and rose bengal scores showed a significant decrease compared with the score in the vehicle group at 7 days (P < 0.05) in the 1000 IU/mL VApal group and at both 3 days (P < 0.05) and 7 days (P < 0.01) in the 1500 IU/mL VApal group. Histological examination revealed recovery of the corneal epithelium, and PAS staining disclosed the recovery of mucin-producing lower palpebral conjunctival goblet cells after 7 days in the 1500 IU/mL VApal group compared with the vehicle group. Results from impression cytology showed a significant increase in density of conjunctival goblet cells compared with that in the vehicle group after 7 days in the 1000 IU/mL VApal group and after 3 and 7 days in the 1500 IU/mL VApal group. There were no significant changes in tear flow in either group. Topical application of VApal at 1500 IU/mL showed greater improvement than 0.1% hyaluronic acid in both fluorescein and rose bengal score and in the density of conjunctival goblet cells.Conclusion: It is suggested that VApal is effective for the improvement of keratoconjunctival epithelial damage associated with tear abnormalities, such as dry eyes.Keywords: cornea, dry eye, hyaluronic acid, vitamin A, wound healing, retinol palmitate